ERGONOMIC ANALYSIS OF PAINTING ACTIVITY ON A PUBLIC EDUCATIONAL BUILDING (Fiep Bulletin - online, 2016)
The following article is aimed to analyze the postures and equipment used in the activities involved to execution the painting in a public education building, and thus propose improvements in postural and ergonomic aspects of the work for this function. For this, it presents the methodology and the ergonomic work assessment as established by NR 17, and use techniques conceptualized as RULA and OWAS, for postural analysis of workers. For ergonomic work analysis (AET), data were collected on a construction site of a public educational building. After initial work environment observation, the study has selected three construction workers who were performing distinct and three sequential stages of painting. The result of this research showed that there is a need to implement a new design to allow changes in the postures for workers. Therefore, this activity needs to eliminate risks rather than treating the symptoms and harmful consequences that could be caused by inadequate posture.
Keywords: Ergonomics. Painting activity. Civil construction.